FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI TANAMAN TEBU (STUDI KASUS PADA DESA SIDOMULYO KECAMATAN BAKUNG KABUPATEN BLITAR) - Neha Febrianti; Eko Wahyu Budiman; Tri Kurniastuti; Rima Dewi Oryza Sativa (BUANA SAINS, 2025)
Sugarcane productivity in Sidomulyo Village, Blitar Regency, remains suboptimal despite the village's strategic role as a supply center for the sugar industry. This study aimed to analyze the factors influencing sugarcane production and to determine the partial and simultaneous effects of capital, labor, land area, seeds, fertilizer, and herbicide on production. A quantitative descriptive method with a survey approach was employed, involving 50 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS version 25. The results of the simultaneous test (F-test) indicate that all independent variables collectively have a significant effect on sugarcane production (F = 61.281; p = 0.000; R² = 0.895), explaining 89.5% of the variation in production. Partially (t-test), labor (p = 0.015), land area (p = 0.000), seeds (p = 0.000), and fertilizer (p = 0.006) have a significant positive effect, while herbicide has a significant negative effect (p = 0.000; coefficient = -0.420). Capital (p = 0.052; coefficient = -0.158) does not have a significant effect at ? = 0.05. The study concludes that to increase sugarcane productivity, farmers should optimize the use of labor, land, seeds, and fertilizer, while reducing excessive herbicide application. Future research is recommended to include variables such as irrigation, technology adoption, and access to credit.